Sources of occupational stress of lecturers in a higher education institution in HCMC - Tran, Thi Cam Tu; Truong , Quang Duoc (Journal of Technical Education Science, 2019)
Stress in the workplace is a growing problem, with extensive costs to individual, organization and society. A cross- sectional study using an online survey conducted in the Universities on Ho Chi Minh city. The population is composed of 244 head teachers and principles. The purpose of this exploratory and analytical study is to answer the question about the sources of occupational stress of lecturers in a higher education institution. For this question, exploratory factor analysis (EFA) and Descriptive Statistics base on Standard Ten Score (McNab, D. et al, 2005) [1] are the two major statistical approaches used for scale purification and data analysis. The finding from this study indicates that there are five major sources of occupation stress: workloads, incomes and benefits, personal development, work- life balance, and control. This research provides a timely insight into the experience of stress within universities. Severals recommendation are suggested for further research in Vietnam.